Percutaneous Coronary Intervention in a Saphenous Vein Graft Failure: A Case Report - Jim, Edmond L. (Universitas Sam Ratulangi, 2024)
Abstract: Recent published data from the Society of Thoracic Surgery (STS) national database displayed that among patients aged >65 years old who survived following an initial coronary artery bypass graft (CABG) operation, rates of repeat revascularization at 1, 5, 10, and 18 years were 2%, 8%, 16%, and 25%, respectively. The most preferred mode of revascularization was percutaneous coronary intervention (PCI). While remain the most frequently used conduits beside left internal mammary artery (LIMA), saphenous vein grafts (SVGs) have high failure rates. Percutaneous coronary intervention in SVGs is associated with an increased risk of distal coronary embolization, commonly resulting in periprocedural MI. We reported a 79-year-old male patient admitted due to progressive symptoms of chronic coronary syndrome. The patient had a history of hypertension and a CABG surgery in 2012. Electrocardiogram showed ischemia and old myocardial infarction (OMI) in inferior leads as well as poor R wave progression in the precordial leads. Transthoracic echocardiogram displayed a normal ejection fraction but impaired left ventricular (LV) diastolic relaxation. Diagnostic coronary angiography revealed a 70% tubular stenosis in proximal part of SVG supplying posterior descending artery, patent LIMA graft to left anterior descending artery, and complex lesion on native vessel (chronic total occlusion in mid right coronary artery). Implantation of drug eluting stent in SVG-posterior descending artery was performed. Direct-stenting PCI technique using undersized-stent was done to prevent any complications. In conclusion, despite the high risk of complications, vein graft intervention was successfully performed without any complications. Since the high rates of in-stent restenosis following PCI in SVGs, long-term dual antiplatelet therapy should be commenced in this patient. Keywords: saphenous vein graft; vein graft intervention; percutaneous coronary intervention